Developmentally controlled changes during Arabidopsis leaf development indicate causes for loss of stress tolerance with age. (28th August 2020) - Kanojia, Aakansha; Gupta, Saurabh; Benina, Maria; Fernie, Alisdair R; Mueller-Roeber, Bernd; Gechev, Tsanko; Dijkwel, Paul P
Abstract: Leaf senescence is the final stage of leaf development and is induced by the gradual occurrence of age-related changes (ARCs). The process of leaf senescence has been well described, but the cellular events leading to this process are still poorly understood. By analysis of progressively ageing, but not yet senescing, Arabidopsis thaliana rosette leaves, we aimed to better understand processes occurring prior to the onset of senescence. Using gene expression analysis, we found that as leaves mature, genes responding to oxidative stress and genes involved in stress hormone biosynthesis and signalling were up-regulated. A decrease in primary metabolites that provide protection against oxidative stress was a possible explanation for the increased stress signature. The gene expression and metabolomics changes occurred concomitantly to a decrease in drought, salinity, and dark stress tolerance of individual leaves. Importantly, stress-related genes showed elevated expression in the early ageing mutant old5 and decreased expression in the delayed ageing mutant ore9 . We propose that the decreased stress tolerance with age results from the occurrence of senescence-inducing ARCs that is integrated into the leaf developmental programme, and that this ensures a timely and certain death. Abstract : Intrinsic stress levels increase as part of the normal leaf developmental programme and this helps the plant to decide which leaves to sacrifice for whole-plant survival during environmental stress.